Strength and Challenges of OBOR Initiative: Indian Perspective. Issue 1 (June 2019) - Singh, Kanwal Deepinder Pal
The One Belt One Road (OBOR) initiative of China is an attempt to 'remake' or recreate the ancient Silk Road or Silk Route, symbolising not only trade network but more importantly cultural interaction. It is an ambitious Eurasian strategy with large financial support, which aims to draw linkages from China to various regions of the world. The connectivity and cooperation presented by China between itself and the rest of Eurasia has two main components: the land-based 'Silk Road Economic Belt' (SREB) and ocean-going 'Maritime Silk Road' (MSR). The 'Belt' includes countries geographically situated on the original Silk Road through Central Asia, West Asia, Russia and Europe and has six main corridors. Countries on the Belt and Road—especially those with underdeveloped infrastructure, low investment rates and per capita income—could experience a boost in trade flow and benefit from infrastructure development. The main challenge for China and for the initiative is the potential for conflicts or geopolitical tensions that could emerge with other powers. This project will increase United States' attention on Central Asia and South Asian region. This will have consequences for the smooth implementation of the strategy. There is an expected resistance from Russia and Russian-led Eurasian Union (EU) that may divide the relevant countries along the route, leaving them torn between choosing to pursue stronger ties with Russia or with China. India also remains cautious of the project and still has not expressed its full support. It sees the initiative not as an opportunity, but as a threat or a form of competition. India's objections are rooted in issues of sovereignty and territorial integrity. For instance, India opposes the China–Pakistan Economic Corridor (CPEC), a pilot project of the trade initiative, due to its route passing through Gilgit-Baltistan, which is a disputed area between Pakistan and India. India has its own agenda of connectivity and cooperation. This article shall first discuss the strengths and challenges of this project and analyse the regional, national and international situations. The Chinese initiative will be discussed, focusing on China's domestic constraints along with regional economic situation and political tensions in neighbourhood. The Indian perspective related to this initiative shall be discussed in detail, including the 'Look East-Act East' policy. Planning and implementation of the project and its impact on bilateral relations shall be discussed. The author shall also analyse the South Asian perspective as a whole, which is plagued by territorial conflicts, bad governance, security threats, impaired transparency, energy crisis, poor infrastructure, fragile institutions and limping economies.